DIAGNOSIS FOR CHAGAS DISEASE: MORE THAN 110 YEARS AFTER ITS DISCOVERY - López Domínguez, Jaime; Ramos Ligonio, Angel; Cessa Mendoza, Alicia; Mora Díaz, Miriam del Carmen; Romero Cruz, Víctor Adolfo; López Monteon, Aracely (Kuxulkab', 2021)
Chagas disease is an infection caused by the parasite 'Trypanosoma cruzi'. In the world, there are million infected people, causing between 10 and 50 thousand deaths annually. The diagnosis of this disease was made by indirect and molecular methods. The selection of the method is based on the clinical phase through which the disease is occurring. However, there is a large number of false positive or negative results, mainly due to three possible causes: genetic variability between strains, cross reactivity with antigens of parasites of the same family and the phase of the disease in which the diagnosis is made. The objective of this work is to make known in a general way the methods of diagnosis, advantages and disadvantages and the perspectives of the diagnosis for Chagas disease.
Keywords: 'Trypanosoma cruzi'; PCR; ELISA; Western blot; Xenodiagnosis